ORGANOLEPTIC INDICATORS AND THE PRESENCE OF AMMONIA IN BEEF INFECTED WITH FASCIOLOSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Nowadays, veterinary sanitary examination of products and its control is one of the most important issue. This article gives information about organoleptically changes and presence of ammonia and its effect to cattle infected with fasciolosis.